Analisis Gramatikal Historis: Memaknai Frasa “Injil Lain” Dalam Surat Galatia 1:6 - Bram M, Prionaray; Sule, Marce (Views : Jurnal Teologi dan Biblika, 2024)
Abstract: In this research, we try to look further into the meaning of other gospels in the Apostle Paul's letter to the Galatians, and strengthen it in the current context. In the phrase another gospel in Galatians 1:6, it is certainly an understanding that needs to be known, in order to understand the existence of the deep and profound existence of the gospel and clearly what the meaning of the other gospel meant by the Apostle Paul is. In this research, researchers used qualitative research methods with literature review methods. Through the results of this research, we have reached two final conclusions about the meaning of the phrase another gospel. First, that the meaning of the other gospel that Paul meant was the teachings that Jews demanded from non-Jews who were members of the community of believers in Galatians. Cultural demands and the Torah are the main points of other gospel messages that are different from the teachings of the Apostle Paul. The second thing, is talking about false teachings that caused confusion in the community of believers in Galatia. Judging from the background of Paul sending the letter, it is clear that the condition of the congregation in Galatia was also attacked by false teachings which caused dissension within the Galatian congregation. Abstrak: Dalam penelitian ini, mencoba melihat secara jauh tentang makna injil lain dalam surat Rasul Paulus kepada jemaat di Galatia, serta implikasinya dengan konteks saat ini. Dalam frasa injil lain di Galatia 1:6, tentu menjadi suatu pemahaman yang perlu diketahui, untuk memahami eksistensi keberadaan injil yang sesungguhnya dan mendalami dengan jelas makna injil lain yang dimaksudkan oleh Rasul Paulus, seperti apa. Pada penelitian ini, peneliti menggunakan metode penelitian kualitatif dengan metode kajian pustaka. Melalui hasil penelitian ini, mendapatkan dua kesimpulan akhir tentang makna dari frasa injil lain, Yang pertama, bahwa maksud dari injil lain yang dimaksudkan oleh Paulus ialah pengajaran-pengajaran yang menjadi tuntutan orang Yahudi kepada non-Yahudi yang tergabung dalam komunitas orang percaya yang ada di Galatia. Tuntutan budaya dan Taurat yang menjadi titik utama berita injil lain yang berbeda dengan pengajaran Rasul Paulus. Hal yang kedua, ialah berbicara mengenai pengajarn-pengajaran yang palsu yang menimbulkan kebingungan dalam komuniatas orang percaya di Galatia. Dilihat dari latar belakang Paulus mengirim surat, bahwa jelas kondisi jemaat di Galatia, juga diserang oleh pengajaran-pengajaran palsu yang menimbulkan pertikaian dalam kalangan jemaat Galatia.